A REVIEW: ENVIRONMENTAL MONITORING APPLICATIONS USING WIRELESS SENSOR TECHNOLOGY - Akshay D. Deshmukh; Dr.Ulhas B. shinde; Krishna M. Biradar (International Journal of Innovations in Engineering Research and Technology, 2021)
With a broad research on wireless sensor technology, the sensor network has proven its significance in today’s modernizing world. In this paper a wireless sensor network system is proposed with open source hardware and software platform i.e Raspberry pi microcomputer which act as a base station, zigbee and a graphical user interface for user friendly application. This system is highly effective both in terms of number of sensors and the type of the sensors. This system provides low cost and feasible solution in the area of environmental monitoring application. A detail review of how actually this system will work and the expected outcome based on theoretical basis are presented in this paper. Raspberry pi is cheap, small, hackable computer linux board. Comparative analysis shows that the performances with wireless sensor nodes using raspberry pi has more successful usage in sensor network domain and remains inexpensive throughout.